The effect of IMT on cycling time-trial performance at ~16°C (cool) and ~26°C (hot) temperatures. - Sharp, C.; Faghy, M. (Journal of Science and Cycling, 2014)
Objective: The purpose of this study was to investigate whether inspiratory muscle training (IMT) improved cycling time-trial (CTT) performance in both cool (~16°C) and hot (~26°C) environmental conditions in well-trained competitive male cyclists. Method: Twelve males were recruited (age: 39.3 ± 12.1 yrs.). Eight participants were assigned to the experimental (IMT) group (VO2max: 63.4 ± 7.6 ml/min/kg; age: 41.4 ± 8.5 yrs.) and 4 to the control (CTRL) group (VO2max: 62.1 ±13.6 ml/min/kg; age: 35.0 ± 18.1 yrs.). The IMT groups were prescribed an IMT training intervention and performance was assessed using a 10-km CTT in cool and hot conditions, pre- and post-intervention. IMT was performed using a pressure threshold loading (PTL) device set at 50% maximal inspiratory pressure (PImax) twice daily for 6-weeks. Results: CTT performance improved in the IMT group in the cool but not the hot. The IMT group went 1.17% faster in the cool (pre- vs. post-intervention: 940.38 ± 91.00 s vs. 929.38 ± 81.75 s) and 0.69% slower in the hot (927.63 ± 79.65 vs. 934.00 ± 74.73 s) (P>0.05). Post-intervention PImax increased in the IMT group both pre- and post-CTT by 25.90% and 22.01%; and 32.54% and 33.63%; respectively in the cool (P<0.05) and hot (P<0.05); the CTRL group observed no significant change. Discussion and Conclusions: IMT increased inspiratory muscle strength (IMS), attenuated inspiratory muscle fatigue (IMF) and improved CTT performance in the cool but not the hot condition. Heart rate increase (HRinc) was attenuated during the hot CTT and an increase in ear temperature (Tear) was counteracted during the cool CTT for a concurrent increase in physiological workload. In conclusion, IMT is a proven ergogenic aid for well-trained cyclists confirming that elite cyclists can still benefit from marginal gains.